Bad boy from Rosebud : the murderous life of Kenneth Allen McDuff - Lavergne, Gary M., 1955- (University of North Texas Press, 1999)
Annotation -- Kenneth Allen McDuff's crimes -- committed after he walked away from the death house a free man! -- would forever change Texas law, earning that state its current reputation for severe and uncompromising justice!-- Really excellent True Crime forces readers to ask tough questions about the imagined day-to-day security they enjoy. Bad Boy does just that, causing law abiding citizens to question the entire justice system and its ability to keep people like them safe ... and people like Kenneth Allen McDuff behind bars!